2022
DOI: 10.1101/2022.06.14.22276168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics and costs of electric scooter injuries in Helsinki: a retrospective cohort study

Abstract: Background and purpose: The incidence of electric scooter (e-scooter) injuries has increased drastically in numerous countries after widespread availability of shared e-scooters. Most publications on e-scooter injuries focus on a specific category of injuries. The economic impact on society from a broader perspective has not been studied. Patients and methods: We performed a retrospective cohort study including all e-scooter-related injuries presented in the three adult emergency departments in Helsinki in 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 5 publications
4
6
0
Order By: Relevance
“…In this context, most operations were performed by orthopaedics, plastic surgery and oral & maxillofacial surgery. This is consistent with other studies demonstrating a high reliance on orthopaedics, plastics or OMFS units for operative management 2,7,19,20,46–48 …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this context, most operations were performed by orthopaedics, plastic surgery and oral & maxillofacial surgery. This is consistent with other studies demonstrating a high reliance on orthopaedics, plastics or OMFS units for operative management 2,7,19,20,46–48 …”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrated that 53% of patients sustained some form of upper limb injury and 50% of patients experienced head injuries. These patterns are again consistent with other studies in Australia and international data 7,16–18,20 . Frequently, riders instinctively extend their arms to break a fall and the head may often strike against the ground or collide with an object.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations